The importance of interpersonal communication in old age - Pitala, Anna (Old Age in the Stream of Life: Reflections on Old Age. Volume 2, 2019)
Stepping man in old age does not mean stability and development, but it gives the potential to understand the meaning of his own life, poses in front of the unit next sentence, the goals that must be achieved. It also connects to a number of constraints and difficulties among other things, with a feeling of loneliness and isolation, which are particularly felt by the elderly. Therefore, the process of proper social communication is an important issue in dealing with the elderly. Proper communication can prevent feelings of humiliation, isolation, and degradation. The article is an attempt to approximate the issues of aging and its worthy experience in terms of proper interpersonal communication. Will be presented causes of difficulties in communicating with older people, the consequences of inadequate communication and ways to build a proper dialogue. The analysis will be based on theoretical knowledge and information gained through non-participating observation.